Animal-assisted therapy as a transforming agent in the health of the older in a Long-Stay Institution in the metropolitan region of Goiânia (Research, Society and Development, 2022)
Animal Assisted Therapy (AAT) is characterized by the use of animals, usually dogs, as adjuncts in the therapeutic process, along with health professionals, as a way of treatment for physical, social and mental improvement. With the increase in longevity and depression, the use of this tool in the comprehensive approach of elderly patients is beneficial. The study aimed to analyze the perception of the elderly about the action of AAT as a transforming health agent. It has a quantitative exploratory character through the application of two questionnaires, one before and the other after the use of Pet therapy, in a Long Stay Institution (ILP) in the metropolitan region of Goiânia - Goiás, where 36 elderly people live, in September and October. de 2022. Inclusion criteria were all elderly people present at the visits and who consented to the research; and the exclusion criteria were the elderly who were not present, those who did not want to participate in Pet therapy, did not consent or when some adversity made it impossible, resulting in the participation of 17 elderly people. The elderly had the same response time and the data were tabulated, analyzed and illustrated by tables and figures. The results show that 94% of the elderly reported a change in mood, happiness, and the mood to perform daily tasks and 88% claimed a decrease in anxiety, improved socialization and relaxation. In addition, the study contributes to knowledge and makes it possible for health professionals and the population to reflect on comprehensive care for the elderly.